2015
DOI: 10.1016/j.techfore.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Regional collaborations and indigenous innovation capabilities in China: A multivariate method for the analysis of regional innovation systems

Abstract: In this study we analyse official Governmental statistics on regional collaborations on innovation in 30 Chinese regions to understand the dynamics of regional collaboration on innovation projects. We propose the use of Ordinal Multidimensional Scaling and Cluster analysis as a novel application to the study of regional innovation systems. Our results show that regional collaborations among organisations can be categorised by means of eight dimensions: public versus private organisational mindset; public versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 101 publications
1
64
0
Order By: Relevance
“…According to these approaches, the most common motive for collaboration is the inter-dependence on resources and knowledge required for developing innovations. Collaboration within these networks integrate the firm with partners, reduce the transaction costs and risks, and correct market uncertainties, as well as offer access to each other's resources, leading to increased productivity (Vega-Jurado et al, 2009;Zeng et al, 2010;Mention, 2011;Maietta, 2015;Zhao et al, 2015;Grimpe & Sofka, 2016). Nelson (1993, p. 511) concluded that "One important feature distinguishing countries that were sustaining competitive and innovative firms was education and training systems that provide these firms with a flow of people with the requisite knowledge and skills.…”
Section: Stream 3: Contextual Determinantsmentioning
confidence: 99%
“…According to these approaches, the most common motive for collaboration is the inter-dependence on resources and knowledge required for developing innovations. Collaboration within these networks integrate the firm with partners, reduce the transaction costs and risks, and correct market uncertainties, as well as offer access to each other's resources, leading to increased productivity (Vega-Jurado et al, 2009;Zeng et al, 2010;Mention, 2011;Maietta, 2015;Zhao et al, 2015;Grimpe & Sofka, 2016). Nelson (1993, p. 511) concluded that "One important feature distinguishing countries that were sustaining competitive and innovative firms was education and training systems that provide these firms with a flow of people with the requisite knowledge and skills.…”
Section: Stream 3: Contextual Determinantsmentioning
confidence: 99%
“…At present, China's R&D activities are conducted mainly by public research institutes and universities (Chang and Shih 2004;Sun and Cao 2015). Thus, public research institutes and universities have become important resources for the creation and dissemination of scientific knowledge in China (Zhao et al 2015). However, because of the influence of the Soviet model of national innovation systems, the activities of S&T innovation in academic institutions have been separated from the industry sector for a long time.…”
Section: Iur Research Collaborations and Policy Actions In Chinamentioning
confidence: 99%
“…Moreover, the second phase of KIP and the ''Pioneer Initiative'' were implemented by CAS in 2011 and 2014, respectively. These S&T policies were introduced to create a favorable institutional environment in which both CAS and domestic universities would continue to contribute to the creation of new knowledge in China (see Zhao et al 2015). To improve scientific performance and increase research output, both CAS and domestic universities strengthened their mutual collaborations in basic research for resource sharing and advantageous complementarities.…”
Section: Bilateral Collaboration Network Of Cas With Universitiesmentioning
confidence: 99%
“…Although embedded in the same national innovation system, the RIS in China may have completely different evolutionary trajectories. Recent studies explored the differences of RIS in China, and found that China's competitiveness depends upon institutional differences among regions (Zhao, Cacciolatti, Lee and Song, 2015).…”
Section: Innovative Clusters and Regional Innovation Systemsmentioning
confidence: 99%